DIFFICULTIES IN LEARNING LITERAL LISTENING OF THE SECOND SEMESTER STUDENTS OF ENGLISH TADRIS STUDY PROGRAM AT STATE ISLAMIC UNIVERSITY OF DATOKARAMA PALU - Afifah, Afifah (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2024)
This research applied a qualitative approach to investigate the difficulties in learning literal listening of the second semester students of English Tadris Study Program at State Islamic University of Datokarama Palu. A structured interview was conducted to answer the research question, “What are the difficulties of learning literal listening of the second semester students of English Tadris Study Program at State Islamic University of Datokarama Palu?” The respondents were seventeen second semester students of English Tadris Study Program of State Islamic University of Datokarama Palu. Through the interview, the researcher discovered several difficulties that the respondents encountered in learning literal listening. The difficulties are the lack of vocabulary to understand words in the materials of listening as well as to understand the details, differentiating minimal pairs in the materials, not being accustomed to the appearance of juncture, not being able to adapt to the speed of speaking of native speakers, not understanding various accents, and the difficulty to focus on the materials